Effect of plasma homocysteine on cardiometabolic multimorbidity among Chinese adults: a population-based and real-world evidence study - Li, Ling; Wang, Jia; Li, Jing; Li, Minqi; Wang, Jie; Long, Tianyao; Zhengliu, Yangyi; Tan, Xuan; Peng, Yiwei; Hong, Xiuqin (Frontiers in Nutrition, 2024)
AimsTo explore the effect of plasma homocysteine (Hcy) on cardiometabolic multimorbidity (CMM) among Chinses adults.MethodsThis study combined a community-based cross-sectional study with a 1:1 matched case–control study using propensity score method among adults aged over 30 years in six districts randomly selected from Hunan Province, China. We recruited 5,258 people, of whom 4,012 met the study criteria were enrolled. CMM was defined as the coexistence of two or more cardiometabolic diseases, including diabetes, hypertension, coronary heart disease and stroke. The plasma Hcy and other laboratory data was measured by chemical automatic detector. Lifestyles and personal characteristics were collected by a questionnaire. Multivariate models were used to explore the associations. We calculated the attributable risk proportion (ARP) for the association of Hcy with CMM. The dose–response relationship was evaluated using restricted cubic splines method.ResultsOf the 4,012 adults, 436 had CMM, with a population prevalence of 10.9%. In the propensity-score-matched case–control study, 828 (414 cases and 414 controls) were included, and those with high plasma Hcy level (>16.2 μmol/L) had a higher risk of CMM than those with lowest level (<10.4 μmol/L) (adjusted OR = 2.83, 95% CI: 1.84–4.36, p < 0.001), with a multivariate ARP of high level of exposure was 64.66% (95% CI: 46.24–77.06%). The largest effect combination of CMM was the coexisting of diabetes, hypertension and coronary heart disease (adjusted OR = 2.26, 95%CI: 1.43–3.57, p < 0.001). An inverse association and dose–response relationship were observed between CMM and plasma Hcy levels. Notably, we recognized a significant mediation effect by C-reactive protein, total cholesterol, triglyceride and waist circumference, and they mediated approximately 8 ~ 23% of the effect of Hcy on risk of CMM.ConclusionOur findings add new evidence to this field that of high level of plasma Hcy was consistently associated with higher risk of CMM among Chinses adults, with the largest effect combination of being coexisting diabetes, hypertension and coronary heart disease. These findings have implications for cardiologists that CMM can be attributable to high level of plasma Hcy, and for decision makers that Hcy has become a public threat that persistently affects cardiovascular health in humans.